CT Imaging Diagnosis in Ovarian Cancer (Eurasian Medical Research Periodical, 2023)
Ovarian cancer is a significant health concern, and early detection and accurate diagnosis are crucial for improving outcomes and survival rates. CT imaging is a widely used diagnostic tool in ovarian cancer, with the ability to detect lesions and evaluate disease extent. In this review essay, we explore the role of CT imaging in the diagnosis of ovarian cancer, including its benefits and limitations. We discuss the potential impact of CT imaging on patient care and highlight the importance of integrating this diagnostic tool into clinical practice. Our findings suggest that CT imaging can play a valuable role in the early detection and diagnosis of ovarian cancer, and we recommend further research to optimize its use in clinical practice.